The Influence of implementing Contextual Teaching and Learning Method on The Arabic Speaking Ability of 11th Grade Students at State Islamic Senior High School 1 Tembilahan - Aisyah, Siti; Wartin, Regina (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2022)
This research aims to investigate the impact of Contextual Teaching and Learning (CTL) method on Arabic speaking skills of 11th-grade students at State Islamic Senior High School 1 Tembilahan. The question is whether the CTL learning model has an effect on the Arabic speaking ability of the students at the school. The population of the study consists of all 11th-grade students at the school, with samples drawn from Natural Science 2 class as an experimental group and Natural Science 3 class as a control group. Observation and testing were used as data collection tools. The results showed that there was a significant effect of the CTL learning model on speaking skills as demonstrated by the the Wilcoxon test. The score of Asymp. sig. (2-tailed) was 0.000, lower than 0.05, leading to the rejection of the null hypothesis and acceptance of the alternative hypothesis, indicating a significant effect of the CTL learning model on the students speaking skills.